I can only imagine - Quaid, Dennis; Finley, J. Michael; Adkins, Trace; Erwin Brothers (Santa Monica, California : Lionsgate, 2018)
Dramatization of the true story behind Bart Millard and MercyMe's hit song.
Originally released as a motion picture in 2018.
Dolby digital 5.1, wide screen 1.85:1.
Features: deleted scenes; MercyMe, the early days; Imagine forgiveness with Bart Millard; Casting I can only imagine; The power of song; Creating Imagine; The music of Imagine; Dennis Quaid, "On my way to heaven"; audio commentary.
Dennis Quaid, J. Michael Finley, Trace Adkins, Madeline Carroll, Brody Rose.
MPAA rating: PG.
In English with optional Spanish subtitles.
Keywords: Millard, Bart -- Drama; Contemporary Christian musicians -- Biography -- Drama; Parent and child -- Drama; Faith -- Drama; Religious films; Fiction films; Video recordings for the hearing impaired; Feature films; Biographical films